Volume 4: Terry Jones Pipeline Technology; Ocean Space Utilization; CFD and VIV Symposium 2006
DOI: 10.1115/omae2006-92167
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-Induced Motion: Model Testing of a Monocolumn Floater

Abstract: The vortex-induced vibrations - VIV have been studied for several fields of engineering due to its occurrence in different structures, such as electrical cables, industries chimneys and offshore risers. Although available an extensive literature describing its fundamental issues, these vortex-induced phenomena still deserve investigation, particularly in the offshore platforms installed in regions with high current speed. Recently, the Vortex-Induced Motions - VIM, a particular case of vortex-induced vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Hence, an experimental investigation was started which focused on VIM responses of small-scale monocolumn floaters in a towing tank. Cueva et al (2006) considered environmental conditions for the Campos Basin and GoM and presented a set of preliminary results. In accordance with other VIM studies, the strong influence of the heading in VIM was noted, increasing the maximum cross flow amplitude from 0.8 to 1.2D.…”
Section: Application Of Model Tests In Relation To Design Verificationmentioning
confidence: 99%
“…Hence, an experimental investigation was started which focused on VIM responses of small-scale monocolumn floaters in a towing tank. Cueva et al (2006) considered environmental conditions for the Campos Basin and GoM and presented a set of preliminary results. In accordance with other VIM studies, the strong influence of the heading in VIM was noted, increasing the maximum cross flow amplitude from 0.8 to 1.2D.…”
Section: Application Of Model Tests In Relation To Design Verificationmentioning
confidence: 99%
“…According to Gonçalves et al [7], in 2005 a partnership between the research group from USPUniversity of São Paulo and Petrobras started a pioneer and intensive experimental research on VIM of monocolumn platforms. Cueva et al [8], Fujarra et al [9], and Gonçalves et al [10] established experimental procedures for VIM tests on monocolumns, besides proposing a more accurate technique for analyzing the outcomes. Moreover, even for very low aspect ratios, the research showed that VIM on monocolumns also presents large amplitudes of transversal motion above reduced velocities of 4.…”
Section: Introductionmentioning
confidence: 99%
“…VIM of cylinders and monocolumn platforms has been widely studied [1][2][3][4][5], which is found to be deeply related to its structural natural frequency and vortex shedding frequency. The vortex-induced vibration (VIV) response is also studied, and the classic 8-shaped orbital trajectories are found for typical cases.…”
Section: Introductionmentioning
confidence: 99%